2004
DOI: 10.1007/s00464-003-9214-6
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic submucosal saline–adrenaline injection in colonoscopic polypectomy: Prospective randomized study

Abstract: Epinephrine injection prior to colonoscopic polypectomy is effective in preventing bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 18 publications
0
39
0
4
Order By: Relevance
“…Studies that included the patients with bleeding tendencies, abnormal coagulograms, or those undergoing anticoagulant therapy were excluded. An overview of the characteristics of the six studies [14], [15], [16], [17], [18], [19] is given in Table 1.
Fig. 1Study selection process.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that included the patients with bleeding tendencies, abnormal coagulograms, or those undergoing anticoagulant therapy were excluded. An overview of the characteristics of the six studies [14], [15], [16], [17], [18], [19] is given in Table 1.
Fig. 1Study selection process.
…”
Section: Resultsmentioning
confidence: 99%
“…Four suitable studies with a total of 1062 patients were identified to examine the efficacy of treatment with submucosal epinephrine injection versus treatment with saline injection or no injection [14], [15], [16], [17]. All four studies compared the rate of postpolypectomy bleeding in patients with a polyp size larger than 10 mm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epinephrine injection to both the stalk and the polyp head,107 as well as looping108 and clipping67 techniques, have been deployed successfully to reduce the risk of bleeding after hot snare polypectomy. Even though injection of epinephrine may only prevent immediate but not delayed bleeding,109 this is the most widely used preventive method, and many authors prefer reserving other techniques only for high-risk patients 5. Some of the reported factors predisposing patients with large pedunculated polyps to a increased risk of bleeding include older age, type of current used, size and histology of polyps, stalk diameter, and use of anticlotting drugs 108,109…”
Section: Complicationsmentioning
confidence: 99%